Analysis of Bacterial Characteristics Using the Electrical Impedance Spectroscopy Method - Dasmasela, Evangelista Militchia Christy; Sugianto, Wahyu; Nur’aidha, Amalia Cemara (Jurnal Pijar Mipa, 2024)
Microorganisms have various shapes, structures, and characteristics. This study uses the method of electrical impedance spectroscopy aimed at identifying and comparing the characteristics of Escherichia Coli, Salmonella Typhi, and Staphylococcus Aureus. Measurements from 1 Hz to 100,000 Hz show that Salmonella Typhi has the highest impedance value at low frequencies. In contrast, Escherichia Coli impedance decreases consistently, and Staphylococcus Aureus decreases sharply after 10 Hz. Significant changes are observed in the mid-frequency range of 100 Hz to 1000 Hz, with Salmonella Typhi showing the highest impedance values at 100 Hz compared to Staphylococcus Aureus and Escherichia Coli. At 100 Hz, Salmonella Typhi has the highest impedance value with a mass of 0,06 grams at approximately 39.000 Ohms, 0,08 grams at 35.000 Ohm, and 10 grams at 34.000 Ohm. This is followed by Staphylococcus Aureus, with a mass 0f 0,06 grams having an impedance value of  23.000 Ohms, 0,08 grams having a high impedance value of 31.000 Ohm, and 0,10 grams having an impedance value of 15.000 Ohm. Escherichia Coli, with a mass of 0.06 grams, has an impedance value of  9.000 Ohms, 0,08 grams with an impedance value of  5.000 Ohms, and 0,10 grams has an impedance value of 5.000 Ohms. Electrical Impedance Spectroscopy is effective for identifying and comparing Escherichia coli, Staphylococcus aureu, and Salmonella typhi as the intrinsic characteristics of bacterial cells more influence impedance than bacterial mass.